Felsőoktatásban tanuló, első generációs kisebbségi hallgatók pályamotivációi - Lánczi Viktória; Ланці Вікторія; Chains Victoria (Видавництво «Код», 2024)
Резюме. Література про соціальну мобільність студентів першого покоління підтверджує, що ці студенти часто починають здобувати вищу освіту у невигідному становищі. (Відсутність) культурного та економічного капіталу, а також освітній рівень їхніх батьків впливають на їхній вибір кар’єри та можливе припинення навчання. У цьому дослідженні ми вивчаємо фактори, що впливають на кар’єрну мотивацію, розглядаючи питання, пов’язані з навчанням студентів-першокурсників з числа національних меншин (N=97).

Abstract. The literature on the social mobility of first-generation students confirms that these students often start higher education at a disadvantage. The lack of cultural and economic capital, along with the educational background of their parents, influences their career choices and potential dropouts. In this study, we explore the factors influencing career motivation by examining issues related to the education of first-year national minority student teachers (N=97). Our aim is to analyze minority teacher candidates’ satisfaction with their skills, training, and future plans using a questionnaire method. The results of the pilot research show that the majority of teacher trainees are first-generation students living in minority communities in Ukraine, currently a war-torn country. According to the results of the pilot research, firstgeneration students make up more than half of the first-year teacher trainees. One of their most prominent motivations for choosing an institution is the ease of access to education, and they choose teacher training mainly to broaden their knowledge. This study examines the career motivations of student teachers from ethnic minority backgrounds. Professional socialization is a lifelong, dynamic process from the moment an individual makes a career choice, influenced by a number of factors. After graduation, the individual incorporates professional expectations into their self-image, leading to the formation of a professional identity. During training, students have the opportunity to acquire skills and knowledge that meet the expectations of the profession, which can lead to a greater sense of commitment to the profession. The target group of this thesis is young members of a Hungarian minority community enrolled in Hungarian-language higher education, specifically in teacher education. Therefore, we consider it important to delineate the characteristics of minority students.

Az első generációs hallgatók társadalmi mobilitásának kérdése széles körben tanulmányozott a nemzetközi irodalomban. Az első generációs hallgatók hátrányosabb helyzetben lehetnek, mint tradicionális hallgatótársaik. Soracco [17] kimutatta, hogy az első generációs hallgatók aránya alacsonyabb, de lemorzsolódási arányuk magasabb. A szerző vizsgálatának célja, hogy azokat a tényezőket hangsúlyozza, amelyek támogatják az első generációs hallgatók felsőoktatási részvételét és sikeres tanulmányait. A közösségi főiskolák módszereit vizsgálva azonosítják az akadályok leküzdésére irányuló intézkedéseket. Az anyagi támogatás és a személyes kapcsolatok hiánya gyakori akadály lehet az első generációs hallgatók számára, a munka melletti tanulás mellett kevesebb idejük maradhat a tanulásra. Az első és második évben kialakult kapcsolatok növelhetik társadalmi tőkéjüket és teljesítményüket. Ivemark és Ambrose [6] kutatása azt mutatja, hogy az adaptáció és az egyetemi részvétel hátterében számos tényező áll. A kulturális tőke, amelyet családjukon és szélesebb környezetükön keresztül szereznek, befolyásolja az adaptációjukat a felsőoktatásba.
Кар’єрні мотивації першого покоління студентів-меншин у вищій освіті
Career motivations of the first generation of minority students in higher education
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00014095
Редакційна колегія: https://sites.google.com/uica.education/nayka/%D1%80%D0%B5%D0%B4%D0%B0%D0%BA%D1%86%D1%96%D0%B9%D0%BD%D0%B0-%D0%BA%D0%BE%D0%BB%D0%B5%D0%B3%D1%96%D1%8F?authuser=0 Зміст:https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-8
Keywords: кандидати на посаду вчителя; студенти першого покоління; кар’єрна мотивація; національні меншини; tanárjelöltek; első generációs hallgatók; nemzeti kisebbségek